Modelagem da capacidade de suporte da área central de Sete Lagoas, MG: subsídios para gestão urbana - Fernanda Costa Ferreira (2019)
The accelerated dynamics of growth and changing of urban spaces has demanded greater investments in urban and environmental management in order to ensure an efficient connection between the two areas. The basic concept for the reasoning of this discussion is about sustainability, one of the main topics debated globally, whose primary thread is the relevance of combining economic development with environmental protection. Furthermore, comes the idea of supporting capacity that has been widely discussed in municipal urban studies, as it aims to identify whether the constructive density-ratio allotted in the urban space is compatible with the natural resources and services of existing infrastructure in the region. Thus, an efficient urban management relies on municipal laws that are structured based on the potential of natural resources of the municipality, considering the population will have their needs being met through these resources as well as maintain a good quality of life. In this sense, the project suggests evaluating whether the urban parameter for occupation established in the Land Use Laws (LUOS) of the city of Sete Lagoas, Minas Gerais, are consistent with the supporting capacity of the land. For this purpose, geoprocessing techniques were applied in data manipulation, in addition to the development of multi criteria analysis that resulted in the mapping of the supporting capacity to the central area of Sete Lagoas, respective in the Centre of town and its neighborhoods. The outcomes were confronted with the current scenario of the space being studied and with possible future conditions spurred by the municipal legislation. Some urban inconsistencies were found in the analyzed area, the major ones being: the existing situation of densification in the Centre of town and in the Paiva’s Characa neighborhood, that is driven by the LUOS urban parameters and the satisfactory supporting capacity of the neighborhoods in the northwest and northeast, still little explored in terms of encouraging urban occupation. This research was applied only in the central area of the city but could at another opportunity be applied throughout the territory of Sete Lagoas to subsidize the updating of municipal laws and the mapping of potential land use. Additionally, it is possible to use the knowledge of this project as a supportive tool in urban management of other municipalities and in the progress of work in the areas of urban and environmental planning, bringing improvements to the quality of life through sustainable development.